A 'Boy's Own' boy zone: The making of fascist men in Emilio De Martino's children's sporting novels. Issue 1 (May 2017) - Martin, Simon
Sports editor of the Corriere della Sera, Emilio De Martino was one of Fascist Italy's most vitriolic sports journalists and prolific authors of sporting fiction. Analysis of his three novels for children published from 1941 to 1943 will consider how his works contributed, first, to the regime's attempt to forge and reinvent both real and imagined traditions through literature, and, second, to Fascism's drive to create a virile, physically and mentally strong youth. Offering a new perspective on Fascism's investment in and exploitation of sport, this article will reveal how a variety of the regime's policies, ideals, myths and goals were propagated and transmitted through fictional stories and adventures. The increasingly radical content and narratives will also show the regime's growing frustration at society's failure to respond to its mobilisation campaigns and increasing desperation following Italy's disastrous entry into the Second World War. Rather than hastening the maturity of young people to create a warrior race ready to risk all for the regime, Fascism's use of 'Boy's Own' heroes and fantasy space will be seen to have contributed to the illusion of strength that young Italians could not match and readiness that the regime could not offer.